2020
DOI: 10.1109/tits.2019.2915273
|View full text |Cite
|
Sign up to set email alerts
|

PC–SPSA: Employing Dimensionality Reduction to Limit SPSA Search Noise in DTA Model Calibration

Abstract: Calibration and validation have long been a significant topic in traffic model development. In fact, when moving to Dynamic Traffic Assignment (DTA) models, the need to dynamically update the demand and supply component creates a considerable burden on the existing calibration algorithms, often rendering them impractical. These calibration approaches are mostly restricted either due to non-linearity or increasing problem dimensionality. Simultaneous Perturbation Stochastic Approximation (SPSA) has been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In contrast with the aforementioned approaches which focus on demand parameters, Balakrishna et al [2007] proposed a more generic solution method for the offline problem based on the Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm that simultaneously incorporates demand and supply side parameters and is applicable to any type of measurement data. Several variants of the SPSA algorithm have since been proposed including weighted SPSA or W-SPSA [Lu et al, 2015a], cluster-wise SPSA or c-SPSA [Tympakianaki et al, 2015], discrete W-SPSA [Oh et al, 2019], PC-SPSA [Qurashi et al, 2019], and gradient approximation [Cipriani et al, 2011]. A more detailed review of the offline calibration problem can be found in Osorio [2019], Djukic [2014].…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the aforementioned approaches which focus on demand parameters, Balakrishna et al [2007] proposed a more generic solution method for the offline problem based on the Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm that simultaneously incorporates demand and supply side parameters and is applicable to any type of measurement data. Several variants of the SPSA algorithm have since been proposed including weighted SPSA or W-SPSA [Lu et al, 2015a], cluster-wise SPSA or c-SPSA [Tympakianaki et al, 2015], discrete W-SPSA [Oh et al, 2019], PC-SPSA [Qurashi et al, 2019], and gradient approximation [Cipriani et al, 2011]. A more detailed review of the offline calibration problem can be found in Osorio [2019], Djukic [2014].…”
Section: Review Of Literaturementioning
confidence: 99%
“…10: A gradient incidence matrix and its corresponding optimal graph with 3 colors At this point, we would like to briefly discuss similarities and differences of this approach compared to variants of the SPSA algorithm. Despite the overt similarity, the variants of the SPSA including c-SPSA [Tympakianaki et al, 2015], w-SPSA [Lu et al, 2015a] and PC-SPSA [Qurashi et al, 2019] do not in fact identify means of partitioning the parameters in the manner that we wish to do (i.e. ensuring that any two parameters in the same partition do not jointly affect a measurement).…”
Section: Graph Coloring Problemmentioning
confidence: 99%
“…This is achieved by transforming the dataset into a new set of variables-the Principal Components (PCs)-which are uncorrelated and ordered so that the first few retain most of the variation present in all of the original variables (Jolliffe, 2002). PCA is an assumption-free procedure that already calculates how ODs are correlated (Prakash et al, 2018;Qurashi et al, 2019). As showed by Djukic et al (2012) and Prakash et al (2018), replacing the OD demand with its Principal Components reduces the problem complexity thus making the ODDE problem simpler.…”
Section: Contribution Statementmentioning
confidence: 99%
“…Calibration of Preday ABM has been performed in several studies, whereby parameters are estimated by Simultaneous perturbation stochastic approximation (SPSA) method with its variants [28,29,31]. However, all studies considered reduction of the dimensionality of the parameter space either by sensitivity analysis (SA) [34] or principal component analysis (PCA) [19].…”
Section: Preday Abmmentioning
confidence: 99%
“…Application of the Preday ABM in simulating various environments requires systematic adjustments or calibration of a large set of parameters (further referred to as ABM parameters), in order to align the associated outputs more closely to the observed values or true output statistics. For that purpose, various optimisation methods are adopted, including primarily gradient-free metaheuristics [28,29,31]. However, Bayesian inference with the recent developments provides a valuable analytical approach for the calibration process [35,36], a great advantage of which is the elimination of necessity to simulate a large sample set in finding the global optima [14,18,20,36].…”
Section: Introductionmentioning
confidence: 99%